Performance-based public management and public procurement processes: a case study - Calero, Roberto (2022)
Objective. To determine the relationship between results-based management and the public procurement processes carried out by the professionals of the Rural Agricultural Productive Development Program (AGRORURAL) of the Huánuco zonal directorate, 2019. Methods. The research is characterized by being of a basic type, with a descriptive-correlational level and a non-experimental design. The Public Management Theory focused on performance budgeting and government contracting is used. For data collection, a survey questionnaire was applied to professionals and officials of AGRORURAL-Huánuco; based on this, Spearman correlation coefficients were estimated. Results. There is evidence of a positive relationship between results-based management and contracting processes (rho=0.71). Likewise, a positive relationship was found between results-based management and the programming phase (rho=0.74), the selection phase (rho=0.85) and the contractual execution phase (rho=0.78) of the contracting processes. Conclusions. It can be affirmed that AGRORURAL employees have an adequate knowledge of results-based management, which translates into efficient hiring processes in line with their proposed goals.